Revision of Neotropical species of Empididae (Diptera) described by Mario Bezzi. VIII. The species described in Hilarempis Bezzi - Rafael, J. A. (Zootaxa, 2012)
Mario Bezzi described 10 Neotropical species in Hilarempis Bezzi, 1905. Six of them are re-described and illustrated fromtype and non-type specimens. Currently all re-described species remain in Hilarempis: H. argentifera Bezzi, 1909, H. bar-batula Bezzi, 1909, H. carinata Bezzi, 1909, H. elegans Bezzi, 1909, H. gymnaspis Bezzi, 1909 and H. xanthocera Bezzi,1905. The primary or secondary type specimens of these species were examined, except for H. xanthocera, and lectotypespecimens are here designated for H. barbatula, H. carinata and H. gymnaspis. The remaining four species of Hilarempis described by Bezzi were either destroyed or could not be located.